Demographics and parasites of African buffalo (Syncerus caffer Sparrman, 1779) in Ruaha National Park, Tanzania. (10th March 2016) - Roug, Annette; Muse, Epaphras A.; Smith, Woutrina A.; Mazet, Jonna A. K.; Kazwala, Rudovick R.; Harvey, Danielle; Paul, Goodluck; Meing'ataki, Godwell O.; Banga, Paul; Clifford, Deana L.
Abstract: The number of African buffaloes ( Syncerus caffer Sparrman, 1779) inhabiting Ruaha National Park, Tanzania, is thought to be declining, but little data exist to determine whether the population is actually in decline. As an initial phase of collecting population data, we conducted demographic surveys, faecal egg counts and gastrointestinal parasite identification in Ruaha's buffalo herds in September 2011 and 2013. Most herds encountered in the two surveys appeared to be in good health, but with fewer calves in 2013 compared with 2011. The herd‐level body condition score was positively associated with the number of calves per 100 cows after adjusting for year, and the lower number of offspring in 2013 could possibly be associated with a below average rainfall in the 2012–2013 rainy season. Mean herd‐level egg counts ranged from 83 to 140 and from 28 to 113 eggs per g faeces in 2011 and 2013, respectively. Haemonchus, Nematodirus, Cooperia and Oesophagostomum spp., as well as coccidian oocysts, were detected in the population. Monitoring herd demographics and baseline health parameters over time will provide insight into population performance, increase the understanding of population stressors and contribute to buffalo conservation within Ruaha National Park and other protected areas of Africa.